Genome-wide characterization of the GmLUX binding preferences and its epigenic features in the soybean genome - Tianxiao, Lv; Xiao, Hong; Wang, Jingxing; Zhang, Ling; Fan, Tian; Huang, Mingkun; Tian, Chang-En; Yang, Hua; Hu, Yufang (Frontiers in Plant Science, 2025)
Transcription factors function in complex regulatory networks to regulate various biological and physiological processes. In soybean (Glycine max), GmLUX, as an important component of the evening complex, plays a critical role in the regulation of soybean flowering regulation. In this study, the genome-wide characterization and epigenetic features of GmLUX binding sites have been analyzed using high-throughput sequencing methods, such as ChIP-seq, Hi-C, histone modification and ATAC-seq. In addition, combined with molecular experiments, GmLUX was found to be able to directly regulate the CO-like gene by facilitating chromatin interactions, suggesting a new regulatory pathway of GmLUX in controlling flowering, which provided the important genomic resources for a further understanding of its regulatory mechanism.